Evaluation of Rural Human Settlement Development Quality and Impact Analysis: Empirical Evidence from China’s Micro Survey? - Sheng Xu; Xichuan Liu; Yu Xiao; Lu Zhang (Land)
Improving the quality of rural human settlements is a key objective in China’s rural revitalization strategy. The purpose of this study is to construct and evaluate the quality of rural human settlements in China from a micro perspective. To achieve this objective, the main tasks include constructing an evaluation system for rural human settlement quality from a micro perspective; measuring the overall and dimension-specific quality levels of rural human settlements using the entropy method based on data from 108 villages in Shandong, Jilin, and Hubei provinces; and further analyzing the influencing factors of rural human settlement quality, focusing on village per capita income, resident population, fire incidents, and agricultural input prices. The findings reveal the following: (1) The overall quality of rural human settlements in Hubei, Shandong, and Jilin is at a moderate-to-low level, with no significant differences among provinces. (2) Among the various dimensions of rural human settlement quality, economic development and public services score higher, whereas living facilities and sanitary conditions score relatively lower, reflecting the inertia of long-term resource allocation and the lagged effects of emerging projects. (3) An increase in village per capita net income and the resident population significantly improves rural human settlement quality, whereas incidents such as village fires and sharp increases in agricultural input prices significantly reduce it. This study provides empirical insights into the mechanisms affecting rural human settlement quality from a micro perspective and offers policy implications for its targeted improvement.